Uganda - Making Finance Work - World Bank (Washington, DC, 2013)
The objective of this report is to contribute to the continuing policy dialogue on financial sector development. It is intended that the analysis and recommendations from this report will contribute towards the preparation and implementation of the National Development Plan (NDP) and the implementation of the Financial Markets Development Plan. The report suggests both policy and institutional reforms to develop rural and agricultural finance. This report has two parts: improving access to financial services and improving the supply of term finance. The first part focuses on three areas: expanding access though the banking system; developing rural and agricultural finance; and improving payments and remittance systems. The second part focuses on three key areas: reforming the pension system; developing the housing finance market; and increasing the private financing of infrastructure. Each chapter has the following structure: the first section provides an overview of the chapter topic; the second presents an analysis of the results of the survey (where applicable) and interviews, and categorizes constraints; the third section provides recommendations to address the constraints.